PENGARUH SIKAP KEWIRAUSAHAAN, NORMA SUBYEKTIF, DAN EFIKASI DIRI TERHADAP PERILAKU BERWIRAUSAHA MELALUI INTENSI BERWIRAUSAHA MAHASISWA - Islami, Novita Nurul (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2017)
This study analyze the influence of the attitude of entrepreneurship, a subjective norm and efficacy themselves against entrepreneurship behaviour through students entrepreneurial intention. The population of this study are the 2010 and 2011 generations of economic education students FKIP Jember University in the academic year 2013/2014 as many as 174 people with the total samples 121 people. The data collection techniques using questionnaires, interviews, and documentation. The method of analysis using Structural Equation Modelling (SEM). The results showed that entrepreneurial attitude and self-efficacy significantly influence entrepreneurial intentions. Entrepreneurial attitude and self-efficacy significantly influence entrepreneurial behaviour. Whereas, subjective norm does not directly affect either the intention of entrepreneurship and entrepreneurial behaviour. Entrepreneurial intentions are also not directly influence the entrepreneurial behaviour. Likewise, an entrepreneurial attitude, subjective norm and self-efficacy also no significant effect on entrepreneurial behaviour intention through entrepreneurship